Strengthening MSME Competitiveness Through Empowerment: Evidence from Padang City Indonesia - Jasril Jasril; Erni Masdupi (Kirana Publisher (KNPub), 2026)
MSMEs play a role in driving economic growth, but in Padang City, they have not developed due to limited capital, lack of innovation, weak bookkeeping, unprofessional management, and low financial/digital literacy. This study aims to describe the strategiesPadang City Cooperatives and MSMEs Service inempowerment of MSMEs in Padang City. This research uses a descriptive qualitative approach with a case study design, with data collection techniques through interviews, observation, and documentation.Twenty MSMEs were interviewed using semi-structured interviews. Thematic analysis was used to analyze the data to determine their experiences in receiving empowerment guidance from the Padang City government.The research results found six main themes of MSME empowerment carried out by the Padang City government, namely increasing human resource capacity, developing MSME institutions, facilitating access to financing, carrying out product innovation, expanding market networks, and creating ecosystem collaboration.This study contributes by placing MSMEs at the center of research and providing context-specific information on policy and practice. It also provides practical recommendations for program sustainability.